2019
DOI: 10.1080/00131881.2019.1660586
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of longitudinal studies of digital learning

Abstract: Biographical notesVilhelmiina Harju M.A. (Ed), is a doctoral student at the Faculty of Educational Sciences, University of Helsinki. Her main research interests are lifelong learning, teachers' professional development, non-formal learning environments, and learning and teaching with digital technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…The National Council for the Teachers of Mathematics [NCTM] (2014) emphasised the idea that technology will support effective teaching and facilitate meaningful learning and that technology could be used appropriately to help students understand mathematics, carrying out reasoning and improving communication skills. Studies have shown that the use of technology in mathematics classrooms is beneficial for students' conceptual learning, positive attitudes and the development of metacognitive skills (Drijvers et al 2016;Harju, Koskinen, and Pehkonen 2019;Olkun, Altun, and Smith 2005;Sinclair 2004). In this regard, it was stressed that technology should be used in primary mathematics education (Higgins, Huscroft-D'Angelo, and Crawford 2019;Kersaint et al 2003).…”
Section: (Page Number Not For Citation Purpose)mentioning
confidence: 99%
“…The National Council for the Teachers of Mathematics [NCTM] (2014) emphasised the idea that technology will support effective teaching and facilitate meaningful learning and that technology could be used appropriately to help students understand mathematics, carrying out reasoning and improving communication skills. Studies have shown that the use of technology in mathematics classrooms is beneficial for students' conceptual learning, positive attitudes and the development of metacognitive skills (Drijvers et al 2016;Harju, Koskinen, and Pehkonen 2019;Olkun, Altun, and Smith 2005;Sinclair 2004). In this regard, it was stressed that technology should be used in primary mathematics education (Higgins, Huscroft-D'Angelo, and Crawford 2019;Kersaint et al 2003).…”
Section: (Page Number Not For Citation Purpose)mentioning
confidence: 99%
“…5G wireless networks are similar to traditional wired computer networks, but regarding their transmission media and related technologies, there is a clear difference between the two. ere are a large number of synonymous, near-synonymous, or up-and-down correlations and juxtapositions among teaching contents in educational resources, and a simple matching search of keywords only will result in a large number of missed detections of teaching resources related to the user's query intention [3]. For this reason, researchers have proposed a concept-semantic query extension method to understand the real needs of learners from the semantic level, grasp the real intentions of learners' queries, and provide learners with knowledge contents with related relationships to meet learners' requirements [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is not possible to draw direct conclusions about the impact of digital technologies on students' learning [12] also the research studies reveal contradicting results: from one side they highlight the close relationship of millennials with information, their media literacy and the ability to use technologies for accessing the information [13], but they also claim that millennials "are not capable of dealing with modern technologies in a way, which is often ascribed to them (i.e., that they can navigate the world for effective and efficient learning and knowledge construction)" [6]. [13].…”
Section: Methodsmentioning
confidence: 99%